The Past and Present of Entrepreneurial Marketing: A Conceptual Insight - Singh, Samridhi (Gyan Management Journal, 2017)
The significance of entrepreneurs and entrepreneurship are extensively recognized. The entrepreneur has become a hero in recessionary times. And the ability to operate, and often also to grow, a business in a challenging business environment is important for society. So there is a need for scholarly studies of entrepreneurship and its intersections with other academic disciplines, such as marketing.Marketing and entrepreneurship have always gone hand in hand. In the recent years it has been acknowledged that the marketing as practiced by entrepreneurs is very different to the concepts offered by the marketing textbooks. Unlike the traditional marketing which is customer centric, entrepreneurial marketing relies on the abilities of the entrepreneur. This conceptual paper integrates the various definitions of entrepreneurial marketing, compares entrepreneurial marketing with traditional marketing and gives a brief overview of the various forms of entrepreneurial marketing of the recent times such as Buzz Marketing, Viral Marketing and Guerilla Marketing.
Keywords: Entrepreneurial Marketing; Traditional Marketing; Buzz Marketing; Viral Marketing; Guerilla Marketing